A case report of open infected clavicle fracture treated with locking compression plate as an external fixator - Nannaware, Mayur S.; Aliasger H. Moaiyadi; Sahil A. Chhabra; Kisan R. Patond (International Journal of Research in Orthopaedics, 2023)
46 year old male presented to emergency department 8 days after fall from bike sustaining trauma to right shoulder and head. On examination revealed that he had open right clavicle fracture (Gustilo and Anderson grade II). Patient was treated with locking compression plate (LCP) as an external fixator. Postoperative follow up was uneventful with no signs of infection and good functional outcome.